Deposition studies of aerosol delivery by nasal cannula to infants. Issue 8 (1st April 2019) - Corcoran, Timothy E.; Saville, Al; Adams, Phillip S.; Johnston, Darragh J.; Czachowski, Michael R.; Domnina, Yuliya A.; Lin, Jiuann‐Huey; Weiner, Daniel J.; Huber, Alex S.; Sanchez De Toledo, Joan; Lo, Cecilia W.
Abstract: Aim: Nasal cannulas are used to provide oxygen support for infants and have been considered as a means for delivering aerosols to the lungs. To measure mucociliary clearance in the lungs of infants with congenital heart defects, we delivered radiopharmaceutical aerosols via a nasal cannula. Here we report on the pulmonary and nasal deposition of these aerosols. Method: A total of 18 infants (median age = 26 days; quartiles = 11‐74 days) performed clearance measurements soon before or after corrective cardiac surgery. The regional aerosol deposition was assessed using gamma camera imaging. Results: Cannula flow rate significantly affected pulmonary dosing. Flow rates useful for oxygen support were associated with low pulmonary deposition (2 L/min; mean, 4.5% of deposited dose; range, 2%‐9%; n = 7) and high nasal deposition. Much lower cannula flow rates increased the pulmonary deposition (0.2 L/min; mean, 33.5% of deposited dose; range, 15%‐51%; n = 5; P = 0.005 vs 2 L/min). The ratio of nose/lung dosing was approximately 26:1 at 2 L/min and 2:1 at 0.2 L/min. Bench studies demonstrated cannula output rates of 10.2 ± 1.7% (2 L/min) and 3.3 ± 0.4% (0.2 L/min) of the loaded nebulizer dose during a 2‐minute delivery. Combining in vitro and in vivo results, we estimate that 0.46% of the loaded nebulizer dose reaches the lungs at 2 L/min vs 1.10% at 0.2 L/min during a 2‐minute delivery. Conclusion: With the delivery system used here, pulmonary aerosol delivery via nasal cannula was very inefficient at the flow rates required to provide oxygen support. Even at low flows, nasal deposition was substantial and local toxicity must be considered.